Redes y comunicación: acompañamientos reflexivos en tiempos de cambio climático - Palacio, Dolly Cristina (2018)
The aspects of a relational perspective are deepened, such as the place-network which off ers a proposal of research and participatory action in the light of relational refl exivity beyond the human in which communication, as a founding phenomenon of the social, is particularly important in the era of socalled information and communication societies. Social Network Analysis (SNA) as a relational epistemology, but also as a method, off ers a unique opportunity to establish relational refl ective processes in times of climate change.